Penyakit Berjangkit: Isu Kesihatan Awam dalam Aspek Sekuriti - Abdullah, Nor Anita; Abdul Rahim, Rohani (Kanun: Jurnal Undang-undang Malaysia, 2012)
Peoples always assumed that the issue of infectious disease was only a social issue which inflicted to a small number of people in the society or to those who were specially infected. Peoples will never deem to expect that the unimportant issue of infectious disease will able to disrupt the human health as well as affecting the national security. In this aspect, the emergence of infectious disease ignores geographical boundaries where most of the countries in the world will suffer the threats of infectious disease as a disaster. Health issue becomes a global issue and at the same time it involves the issue of national security. All sorts of conflicts will arise when people in the society will blame the responsible authority for the failure of controlling and preventing the infectious diseases. The questions to be analyzed: whether the recent existence of infectious disease could threaten the national security or just a social issue per se? If it is a need to protect the people, whether the law is responsible in performing the protection and control of infectious diseases and at the same time able to protect the national security from the threat of infectious diseases? Keywords: Infectious diseases, public health, security, disaster, laws